Rural Muslim Empowerment Through the Development of Applicable Technology - Rohman, Thofiqur (International Conference of Moslem Society, 2019)
This paper focuses on the process of empowering rural Muslim communities by improving the quality of life through the development of appropriate technology to be renewable. Renewable technology is an effort to develop simple technology that is needed by the community, and the practice of using potential in the community environment, so that it can be updated at a low cost. The research setting is the Muslim community of Sokawera Village, Cilongok District, Banyumas Regency. The background of the problem is to find public poverty and general school dropouts, the abundance of manure waste, the lack of funds to buy fertilizers, and the imbalance between low economic capacity and the ownership of abundant potential in the form of community culture raising livestock. This type of research is qualitative research by conducting exploration through interviews, observation and forum group discussions. Data analysis is done by searching and compiling data systematically from the results of interviews, observation and forum group discussions. The findings of this study are in the form of a model of empowering rural Muslims through the development of appropriate technologies for renewable. The model is named after the House of Empowerment. Rumah Empowerment is a concept in carrying out the empowerment process from the beginning to the end. In this concept, there are five processes. The five processes must be carried out coherently so that the target of empowerment is maximally achieved and can be sustainable. The five processes referred to, namely; 1) Mapping the subject of empowerment, 2) Coordination, 3) Expansion of Empowerment, 4) Evaluation, 5) Improvement.